Designing a mobile attendance application prototype for KPM Indera Mahkota / Syahid Ali - Ali, Syahid (2014)
Taking and processing student attendance is essential to the academic process which is under the responsibility of Jawatankuasa Disiplin Kolej (College Disciplinary Committee) of Kolej Profesional MARA Indera Mahkota. However, manual attendance processes have problems such as data inaccuracies, repetitive processes, lost of attendance data and submission problems. With the popularity of mobile phone applications among users; a mobile attendance application is one of the solutions. A mobile application must be easy to use to attract users to use it consistently. A mobile design guideline is needed to guide the design process. The aim of this study is to design a mobile attendance application prototype using the Three Layer Design Guideline. The project begins with identifying user requirements via interviews and the results from the analysis shall be the input of the design process. Prototype is then developed to demonstrate the design proposed. The developed prototype can be used as a basis for the development of a complete mobile attendance application for KPM Indera Mahkota and serves as a proof to improve the Three Layer Design Guideline in the future.